Spontaneous Hematoma of the Right Large Lumbar Muscle, Hemorrhagic Vasculitis, Multiple Arterial Thrombosis in the Background of COVID-19 - A. N. Kazantsev (Neotložnaâ Medicinskaâ Pomoŝʹ, 2022)
Patient A., 65 years old, male. He was admitted to the City Alexandrovskaya Hospital with complaints of fever within 5 days to 39.0°C, dry cough, shortness of breath during exertion, pain in the right ﬂ ank of the abdomen and right lumbar region for 7 days. Three days earlier, the patient had received a positive polymerase chain reaction test for the presence of SARS-CoV-2. Examination of the patient revealed a hemorrhagic rash on both legs. The patient was consulted by a dermatovenerologist, acute infectious hemorrhagic vasculitis, bullous form, was diagnosed.According to multispiral computed tomography with angiography (MSCT AG) of the abdominal organs: the psoas major muscle on the right was thickened, its structure was determined by the accumulation of the contents of hemorrhagic density with signs of partial lysis in the marginal zone, with a total size of 52x48x148 mm. No data available for aortic aneurysm / dissection. The patient denied the presence of injuries, taking anticoagulant drugs. The psoas major muscle hematoma was regarded as spontaneous hematoma against the background of coagulopathy caused by COVID-19.According to the MSCT data of the chest organs, it was visualized: polysegmental lesion in both lungs, numerous areas of compaction of the lung tissue were determined by the type of ground glass, with zones of consolidation and reticular changes in the structure. The degree of damage to the lung tissue was 55%.In view of the fact that the patient had data for the presence of a hematoma of the psoas major muscle on the right, as well as hemorrhagic vasculitis, anticoagulant therapy was contraindicated. Laboratory tests revealed an increase in the level of procalcitonin up to 12.8 ng/ml, C-reactive protein up to 135.1 mg/l, leukocytes up to 13.46 10^9/l, ferritin up to 532.2 ng/ml, D-dimer up to 1145 ng/ml. A multidisciplinary council (infectious disease specialist, general surgeon, therapist, pulmonologist, vascular surgeon, dermatovenerologist, septologist) decided to revise and drain the hematoma of the psoas major muscle on the right, as a likely source of sepsis (increased procalcitonin). Under intravenous anesthesia, the hematoma was opened posteriorly peritoneally, evacuated (about 300 ml in volume), 2 drains were installed. On the 10th day after the operation, a control MSCT was performed, according to which the hematoma of the right psoas muscle decreased in size by half. A decision was made to remove the drains.On the 13th day after admission to the hospital, the patient developed pain in the right forearm, hand, left leg and foot. Performed MSCT revealed hypertension of the arteries of the upper extremities and arteries of the lower extremities: thrombosis of the distal third of the brachial, ulnar and radial arteries; thrombosis of the superﬁ cial femoral artery (PFA) on the left. An anticoagulant therapy was started (heparin 7500 IU intravenously in a stream with subsequent transfer to continuous intravenous administration using an infusion pump with an initial rate of 1000 IU per hour, under the control of APTT with an indicator reaching 1.5–2.5 times higher than the norm), disaggregant therapy (acetylsalicylic acid 100 mg once a day), analgesic therapy (ketorol 1.0 ml/m). An emergency simultaneous operation was performed: thrombectomy from the brachial, radial, and ulnar arteries on the right under local anesthesia (transverse arteriotomy of the brachial artery, Fogarty catheters 3F, 5F) with satisfactory antegrade and retrograde blood ﬂ ow; plus under spinal anesthesia, an attempt was made to thrombectomy, Fogarty 5 catheter passed freely, a weak retrograde blood ﬂ ow was obtained, but after 3 minutes, repeated thrombosis of the PBA developed). That followed by femoral-popliteal prosthetics (above the knee joint gap) with a synthetic prosthesis “Ekoﬂ on” with obtaining a satisfactory pulsation distally.On the 21st day after the operation, the patient was discharged from the institution in a satisfactory condition.